Ride, ranger, ride - Kane, Joseph, 1894-1975; McGowan, Stuart; McGowan, Dorrell; Autry, Gene, 1907-1998; Republic Pictures Corporation; Cinetel Films ([Los Angeles, CA] : Republic Pictures Corporation, 1936)
Gene is a Texas Ranger working under cover to protect an Army wagon train full of ammunition and supplies. The Army doesn't believe him at first, until the Commanches arrive.
Originally released as a motion picture in 1936.
Gene Autry, Smiley Burnette, Kay Hughes, Monte Blue, Max Terhune, Robert E. Homans, Lloyd Whitlock, Chief Thundercloud and the Tennessee Ramblers.
Cinematographer, William Nobles; editor, Lester Orlebeck.
In English.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed December 4, 2015).
Keywords: United States. -- Army. -- Cavalry -- Drama; Texas Rangers -- Drama; Comanche Indians -- Drama; Western films; Feature films; Internet videos; Short films; Streaming video